Pakistan's Higher Education System—What Went Wrong and How to Fix It - Hoodbhoy, Pervez (The Pakistan Development Review, 2009)
Publisher: Pakistan Institute of Development Economics, Islamabad KerkoCite.ItemAlsoKnownAs: 10.30541/v48i4IIpp.581-594 10.30541/v48i4iipp.581-594 10/ghzt9f 2339240:WS4MICAT 2405685:JS95GND5

The gender digital divide in rural Pakistan: How wide is it and how to bridge it? - Siegmann, K. A. (2009)
textabstractWhile Pakistan’s National Information Technology (IT) Policy aims at harnessing the potential of information and communication technologies (ICTs) for development, especially in the underserved rural areas, it ignores the role of existing gender inequalities on the possible benefits of ICTs. We have investigated aspects of the ‘gender digital divide’ in rural areas of Pakistan in order to enable an evidence-based gender-sensitive revision of the policy as well as ICT-related interventions from which both females and males gain. The study took place in four of the most marginalized rural districts of the country where this divide is likely to be most pronounced. We found mobile phones to be the ICT that is most commonly available in rural Pakistan. Radios and TV sets are the second most widespread technologies in marginalised rural areas. However, mobile sets at hand are largely owned by women’s husbands, fathers and brothers, whose permission to make calls is required by a large share of all female respondents. I, therefore, argue that availability and gendered use of ICTs are two different things altogether. Social norms related to women and girls’ access to education as well as regulating their mobility prevent them from using ICTs. These norms have to be taken into account in policies and interventions to ensure women and girls’ access to and beneficial use of ICTs.
KerkoCite.ItemAlsoKnownAs: 2339240:G8SKSDEL 2405685:8D4Z2825

Information and communication technology (ICT) education in the city school, Pakistan - A success story in the large-scale introduction of the UK National Curriculum's ICT component in Pakistan - Ali, I.; Proctor, J. (Aslib Proceedings, 2005)
Purpose - In an age of information technology some developing countries are more vulnerable than others to international competition through failure to utilize fully the benefits of an ICT culture. The authors suggest that the strategies in response must include a radical review of attitudes and methods of delivery of ICT in schools and give as an example the recent experience of The City School, the nationwide schools' organisation in Pakistan with whom they are employed. Design/methodology/approach - The authors review the current position of ICT in schools in Pakistan and suggest as a model of development, for schools of a corresponding standing, that of The City School. They describe how The City School responded to ICT, ensuring that all its pupils would have access to the most modem of ICT courses. Discusses how the decision to implement a complete change, or revolution, in teaching ICT was brought about in a relatively short time. It discusses the nature of the programme, how it was organised, the materials required and the outcomes of its implementation including its outstanding success with pupils and their parents. Findings - The authors chronicle the historical developments within The City School that brought about radical change within a comparatively short period and identify careful planning, training, and the motivation of stakeholders, i.e. pupils, teachers and parents, as key elements in its successful implementation. Originality/value - The authors suggest that The City School experience provides a model that may be emulated by schools elsewhere in both developing and industrially developed countries.
Place: Bradford Publisher: Emerald Group Publishing Limited WOS:000228458000003 KerkoCite.ItemAlsoKnownAs: 10.1108/00012530510589092 2339240:5LZA5PP2 2405685:IZSECS4Z
Keywords: Pakistan; communication technologies; design and development; schools

Development of a cadre of teacher educators: some lessons from Pakistan - Khamis, Anil; Sammons, Pamela (International Journal of Educational Development, 2004)
This article is based on an educational innovation, the creation of a cadre of teacher educators, in the developing world. Professional development teachers (PDT) were trained in an in-service two-year teacher education programme leading to a Masters of Education (M.Ed.) degree. The PDTs were expected to play three roles in their home schools upon completion of the degree programme: (a) exemplary teachers; (b) teacher educators; and (c) change agents within their home schools to effect improvement. This article reviews education in Pakistan and the innovations that have come to inform the need to focus on teacher education as a primary area of investment and presents findings of a three-year longitudinal study of a selection of PDTs trained at the Aga Khan University’s Institute for Educational Development (AKU-IED). The main findings of the study indicate that teachers benefited significantly as individuals with enhanced career prospects, identified themselves more and preferred the role of teacher educators as opposed to classroom-based teachers, and sought opportunities outside their own schools but their role as change agents was more limited. Those teachers who maintained links with their schools beyond the three-year bonding period (a condition of being admitted to study for the M.Ed.) varied in the extent to which they managed to initiate and sustain school improvement efforts as indicated by changes in the structures and relationships within schools affecting the teaching–learning offered to pupils.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.ijedudev.2003.11.012 2339240:HZWD3HPL 2405685:VR29AWRC
Keywords: Development; Educational policy; International education; Pakistan; School improvement; Teacher education

National Education Policy - Ministry of Education and Federal Training (Pakistan) (2009)
KerkoCite.ItemAlsoKnownAs: 2405685:C2TJ7SEC

Pakistan - Learning and Educational Achievements in Punjab Schools (LEAPS): insights to inform the education policy debate - Andrabi, Tahir; Das, Jishnu; Khwaja, A. I.; Vishwanath, T.; Zajonc, Tristan (World Bank, 2008)
This report shares the findings of first round of the Learning and Educational Achievement in Punjab Schools (LEAPS) survey carried out in all the public and private schools offering primary level education in 112 villages of the province. This survey includes learning outcomes for 12,000 children in Class III in Urdu, English, and Mathematics together with detailed information on the beliefs and behavior of schools, teachers and parents. This large and independent exercise provides critical information on every aspect of the educational marketplace, including performance of all types of schools in select districts of the province. This report presents findings from the first round of the survey in 2003 along with trends for a few key outcomes between 2003 and 2007; a further report will incorporate all other information from the four rounds collected between 2003 and 2007.
KerkoCite.ItemAlsoKnownAs: 2339240:JNUWM4UI 2339240:TTHQC2V4 2405685:9ZDCBLKK 2405685:LKSB8HEW

The relative effectiveness of government and private schools in Pakistan: Are girls worse off? - Aslam, Monazza (Education Economics, 2009)
KerkoCite.ItemAlsoKnownAs: 10.1080/09645290903142635 2339240:JX9ZURYR 2405685:B2Y3PBB2

Empowerment of Women through Distance Education in Pakistan - Bukhsh, Qadir (2007)
The present study was undertaken to highlight the gender disparities of Pakistan as well as at regional and international level. The study, measured the comparative outcome of formal and non-formal system of education in Pakistan. To achieve the desired goal, documentary analysis was considered appropriate. The number of schools and enrollment during the years 2001 to 2004 of the formal system for primary, middle and high level was considered and enrollment during the year 198-1999 and 2004 for Secondary School Certificate to Ph.D level of non-formal system was considered. Data was analyzed in term of percentage and average. It was found that enrollment of female is less than male in formal system while enrollment of female is higher than male in non-formal system of education in Pakistan. (Contains 16 tables.)
Issue: 4 Publication Title: Online Submission KerkoCite.ItemAlsoKnownAs: 2339240:GH4W93KG 2405685:HC78WJKZ
Keywords: Access to Education; Computer Uses in Education; Distance Education; Elementary Secondary Education; Empowerment; Enrollment Trends; Females; Foreign Countries; Gender Differences; Nonformal Education; Postsecondary Education; Womens Education

Investigating educational change: The Aga Khan University Institute for educational development teacher education for school improvement model - Khamis, Anil; Sammons, Pamela (International Journal of Educational Development, 2007)
This article continues the analyses of the impact of an innovative teacher education programme aimed at school improvement in a developing country context (A. Khamis, P. Sammons, 2004. The development of a cadre of teacher educators: some lessons from Pakistan. International Journal of Educational Development, 24(3), 255–268). Building on recent publications that have analysed outcomes of the teacher education programme and how the cadre of teacher educators has worked to initiate improvement in schools in Pakistan. The article considers the ‘teacher education for school improvement model’ based on findings from the case studies of nine co-operating school. Lessons are presented to further inform the development of teacher education programmes and the measurement of effectiveness of such programmes in developing country contexts. The article further considers relevant international research on educational change and reform to draw further lessons. These lessons include the need to pay greater attention to the cultural contexts and milieu in Pakistan, and the need to create models of school improvement and teacher education that originate within developing country contexts rather than the adaptation of European/North American models that are based on sources of data in those contexts. The article concludes by arguing for the need to develop better theoretical understandings from the current innovations underway and placing the onus on intervening agencies to better inform educational change strategies promoted in developing country contexts.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.ijedudev.2006.12.006 2339240:9NIU3EAU 2405685:AVG9NPXF
Keywords: Developing countries; Educational change; Innovation; Pakistan; School improvement; Teacher education

National Education Policy 2009 - Ministry of Education (Government of Pakistan, 2009)
KerkoCite.ItemAlsoKnownAs: 2339240:K3JILXD8 2405685:9ZZ2SVMJ 2405685:M94ZQF5Z

Study on Role of Radio for Rural Education in Pakistan - Jumani, Nabi Bux (2009)
It was found that the majority of the listeners possessed radio sets and was getting benefit from the educational programmes of radio. The programmes were informative and motivating. The strategies of radio for rural education were appreciable because these infused mobility, widened horizon of rural people and focused attention on the goals and problems of rural people. It could be used to enhance literacy (through distance and non-formal education). The producers/comperes were found keenly interested in their job. It was revealed that priority was given to education and rural development programmes of radio. Programmes needed detail and summary at the end. Furthermore language was not easy. Mobile radio station was needed for rural educational programme to cater to the needs of far flung areas. School broadcast (distance and non-formal teaching) was the need of the day. Social workers/opinion leaders opined that there was need of developing self reliance. Radio provides guidance to rural people in solving the problems of rural development. They felt the need of starting school broadcasting. Radio was being utilized for apprising villagers with their problem. There was need of maintaining more educational programmes. Rural programmes were to be in mother tongue. It was recommended that for educational purposes Radio Pakistan and AIOU may produce programmes which have their strong links/roots in the surroundings of the rural people. Radio schools like Interactive Radio instruction (IRI) may be used for effective teaching learning process in rural areas. Time of educational programmes should be enhanced. Programmes like radio rural forum may be started as well as open broadcasting should be adopted for rural development programme. (Contains 5 tables.)
ISSN: 1302-6488 Issue: 4 Publication Title: Online Submission KerkoCite.ItemAlsoKnownAs: 2339240:6QWQ77L4 2405685:H456VCTC
Keywords: Distance Education; Educational Technology; Foreign Countries; Instructional Effectiveness; Nonformal Education; Radio; Rural Areas; Rural Development; Rural Education; Teaching Methods

IDRC in Pakistan - IDRC (IRDC, 2009)
KerkoCite.ItemAlsoKnownAs: 2339240:CFIXEMFB 2405685:CTCDCYPM

Literacy Promotion through Mobile Phones - Miyazawa, Ichiro (UNESCO, 2009)
KerkoCite.ItemAlsoKnownAs: 2405685:ITZEFIGS

Urdu version of Sesame Street from April - Mohiuddin, Saeed (The News International, 2009)
Pakistani children would be able to watch the Urdu version of Sesame Street – the most-watched children’s television show in the world – five days a week on both PTV 1 and PTV 2...
KerkoCite.ItemAlsoKnownAs: 2405685:JFFPPRY2

Research in Difficult Settings: Reflections on Pakistan and Afghanistan - Khattak, Saba Gul (International Development Research Center (IDRC), 2009)
KerkoCite.ItemAlsoKnownAs: 2339240:XSWXCUZW 2405685:MES6JCMC
Keywords: ⛔ No DOI found

Building back better: post-earthquake responses and educational challenges in Pakistan - Kirk, Jackie (UNESCO, 2008)
KerkoCite.ItemAlsoKnownAs: 2339240:86QE8UYC 2405685:IPHTPGVQ

Assessment of Computer-Based Nutrition Education Model in Primary Schools of Lahore, Pakistan - Elmadfa, I.; Siddique, A. (Annals of Nutrition and Metabolism, 2009)
Place: Basel Publisher: Karger WOS:000270827202303 KerkoCite.ItemAlsoKnownAs: 2339240:ZAGF2JAT 2405685:327QGPS7
Keywords: ⛔ No DOI found

The effect of gender differences in primary school access, type, and quality on the decision to enroll in rural Pakistan - Lloyd, Cynthia B.; Mete, Cem; Sathar, Zeba A. (Economic Development and Cultural Change, 2005)
KerkoCite.ItemAlsoKnownAs: 10.1086/427042 2339240:EA862BFY 2405685:8SGRK3XF

The Use of Information and Communications Technology (ICT) To Improve Access to In-Service Teacher Education Programmes For Educational Development in Pakistan - D‘CRUZE, Melaine (The Turkish Online Journal of Distance Education, 2009)
The use of ICT and distance education in the delivery of professional developmentprogrammers for in-service teachers to improve access to educational opportunitiesis explored in this article. Further, the link between teacher development and thedevelopment of human capital to aid educational and national development isdiscussed. The role of ICT and distance education is highlighted in enabling thisventure which eventually leads to overall educational and national development.
KerkoCite.ItemAlsoKnownAs: 2339240:8HUGUZKS 2405685:ZSFVUL79
Keywords: ⛔ No DOI found

Sisimpur’s reach and educational impact: Evidence from a national longitudinal survey of a Sesame Street project in Bangladesh. - Lee, H.J. (Sesame Workshop, 2009)
KerkoCite.ItemAlsoKnownAs: 2339240:KIX4GIDD 2405685:JU9AZWT2 4803016:35JDVYDE

Tuned in to Student Success: Assessing the Impact of Interactive Radio Instruction for the Hardest-To-Reach - Ho, Jennifer; Thukral, Hetal (Education Development Center, 2009)
This study reviews student assessment data collected from 15 EDC projects to determine the impact of interactive radio instruction (IRI) on student achievement in hard-to-reach areas.
KerkoCite.ItemAlsoKnownAs: 2339240:4A5246Z6 2339240:62K8ZTKG 2339240:J5GYXMFY 2405685:V73WF7EZ 2405685:VF7IM4CW 2405685:WH7JDBUP
Keywords: ___working_potential_duplicate; ⛔ No DOI found

E-Learning as Part of Disaster Recovery Planning - Hanssen, Graeme M.; Rana, Tohid Ahmed (2007)
The world has recently witnessed large natural disasters with the Asian tsunami, the Pakistan earthquake, etc, which has resulted in loss of life measured in hundreds of thousands. One or two years later surveys of reconstruction work have revealed less than 25% of schools have been re-established, implicating long term economic and social consequences. Disaster Recovery planning could include rapid deployment of E-learning systems adapted to disaster zones, even with an apparent lack of broadband telecommunications infrastructure. This paper proposes technically innovative solutions to the rapid re-starting of education in disaster-struck communities by introducing the concept of a mobile E-school. Planning for Disaster Recovery could include the solutions proposed herein, as it is also possible to imagine in this Globalization World that budgets of wealthier nations encompassing these concepts. (Contains 1 figure.)
Publication Title: Online Submission KerkoCite.ItemAlsoKnownAs: 2339240:TNQWGH3K 2405685:7VPDA68G
Keywords: Computer Uses in Education; Distance Education; Educational Technology; Emergency Programs; Foreign Countries; Global Approach; Natural Disasters; Online Courses; Telecommunications; Virtual Classrooms

Improving Educational Quality through Interactive Radio Instruction - World Bank (2005)
KerkoCite.ItemAlsoKnownAs: 2339240:P8RFXRRD 2405685:NJE9HJMQ

Emerging Technologies: An Overview of Practices in Distance Education - Hussain, Irshad (Journal on School Educational Technology, 2007)
In contemporary society, information technologies and communication technologies (ICTs) are playing crucial role in dissemination of knowledge and information the world over. Universities/ higher education institutions, particularly distance education universities in developed countries are making best use of these technologies for effective and interactive teaching learning process. Developing countries are also trying to adopt the model of developed countries according to their resources and circumstances. Distance education universities in developed countries like United States of America and United Kingdom are using advanced (emerging) technologies such as computers, Internet (World Wide Web) satellite communication, teleconferencing (videoconferencing and audio conferencing) and virtual reality in education and training. In developing countries like India, Pakistan and Thailand, distance education universities are using Radio, Television and Internet for teaching learning purpose and students support services. They are using computers mostly for office work. They are trying to adopt advanced technologies like developed countries but they have some limitations of resources (human & material resources). In future it is hoped that developing countries will also be using emerging technologies for teaching learning purpose.
Publisher: i-manager Publications KerkoCite.ItemAlsoKnownAs: 10.26634/jsch.3.2.751 2339240:C2AIV4L4 2405685:C5QWP7I4
Keywords: Case Studies; Computer Mediated Communication; Distance Education; Educational Development; Educational Practices; Educational Technology; Educational Television; Foreign Countries; Influence of Technology; Information Networks; Online Systems; Open Universities; Technological Advancement; Technology Integration; Technology Uses in Education; Telecommunications; Virtual Universities